استخدام روابط الجذب الخلفية في دراسة التشابك القطاعي في سورية خلال الفترة (2006-2013) - حيدر, عز الدين; يوسف, حسين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
In this study, we examined the input and output tables of the Syrian economy during the period 2006-2013. We calculated the direct back-pull links of the economic sectors during the considered period to determine the leading economic sectors in the Syrian economy. The best sector is wholesale and retail trade sector with an average value of 2.13 means that the production of one lira in the wholesale and retail trade sector will generate a demand of 2.13 pounds. This sector has maintained a value of more than 2 in most years of the studied period. We also note existence a group of sectors that can be described as leading economic sectors Because of high value front links, such as Textiles, water, electricity, construction, community services and personal services, while direct back-pull links of the leather sector were only 1.14. We also found a significant statistical impact between each of the leading sectors and the rest of these sectors. يهدف هذا البحث الى دراسة جداول المدخلات والمخرجات الخاصة بالاقتصاد السوري خلال الفترة بين 2006 و2013 ومن ثم حساب روابط الجذب الخلفية المباشرة للقطاعات الاقتصادية خلال الفترة المدروسة لتحديد القطاعات الاقتصادية الرائدة في الاقتصاد السوري. تم التوصل إلى عدة نتائج أهمها أن أفضل القطاعات الاقتصادية كان تجارة الجملة والمفرق بمتوسط قيمة 2.13 بمعنى أن إنتاج ليرة واحدة في قطاع تجارة الجملة والمفرق سيقوم بتوليد طلب قدره 2.13 ليرة من إنتاج باقي القطاعات, حيث حافظ هذا القطاع على قيمة تفوق 2 في أغلب السنوات المدروسة, كما لاحظنا وجود مجموعة من القطاعات يمكن وصفها بأنها قطاعات اقتصادية قيادية لتحقيقها قيمة مرتفعة من حيث روابط الجذب الخلفية الكلية وهي النسيج والماء والكهرباء والبناء والتشييد وخدمات المجتمع والخدمات الشخصية , بينما كانت أقل قيمة لروابط الجذب الخلفية الكلية لدى قطاع الجلود ب 1.14 فقط. كما وجدنا أثر ذو دلالة إحصائية بين كل قطاع من القطاعات الريادية وبين باقي هذه القطاعات.